2022
DOI: 10.1186/s40814-022-01112-1
|View full text |Cite
|
Sign up to set email alerts
|

Online singing interventions for postnatal depression in times of social isolation: a feasibility study protocol for the SHAPER-PNDO single-arm trial

Abstract: Background Postnatal depression (PND) affects 13% of new mothers, with numbers rising during the COVID-19 pandemic. Despite this prevalence, many women have difficulty with or hesitancy towards accessing pharmacological and/or psychological interventions. Group-based mother-baby activities, however, have a good uptake, with singing improving maternal mental health and the mother-infant relationship. The recent lockdowns highlight the importance of adapting activities to an online platform that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 39 publications
1
7
0
Order By: Relevance
“…The online format was implemented directly in response to the suspension of inperson groups due to social distancing restrictions and provided an opportunity to explore whether similar ingredients and mechanisms to improved mental health might be observed by participating online as in person. Our study helps interpret the ndings of the feasibility trial (27) by mapping out programme ingredients that seemed to trigger mechanisms which then impacted PND symptoms, as well as identifying ingredients unique to online delivery such as being able to sing on mute at home which led to increased con dence in singing.…”
Section: Discussionmentioning
confidence: 93%
See 3 more Smart Citations
“…The online format was implemented directly in response to the suspension of inperson groups due to social distancing restrictions and provided an opportunity to explore whether similar ingredients and mechanisms to improved mental health might be observed by participating online as in person. Our study helps interpret the ndings of the feasibility trial (27) by mapping out programme ingredients that seemed to trigger mechanisms which then impacted PND symptoms, as well as identifying ingredients unique to online delivery such as being able to sing on mute at home which led to increased con dence in singing.…”
Section: Discussionmentioning
confidence: 93%
“…For example, previous research on virtual choirs has shown that participants engaging virtually report lower and more variable social presence than participants of in-person choirs (29). Yet in the M4M-online intervention, the outcome ndings suggested comparable bene ts to mental health in the in-person intervention (20,27). This raises the question as to whether the 'core' ingredients most responsible for effects were nonetheless still present, even if there were changes to other ingredients that may have been more peripheral.…”
Section: Introductionmentioning
confidence: 88%
See 2 more Smart Citations
“…The scale-up of the community M4M is underway as part of the larger SHAPER programme [ 25 ], but the COVID-19 pandemic led to the development of an online adaptation of M4M (SHAPER-PNDO), presented here. This was a 6-weekly online intervention adapted from the original community 10-week M4M, as described in the published protocol [ 26 ]. To reduce the risk of disengagement by participants that may happen with online interventions, the duration was shortened from the 10 weeks to 6 weeks, as this is the earliest time point that showed significant antidepressant effects in the community M4M study [ 24 ].…”
Section: Introductionmentioning
confidence: 99%